Efficacy and safety of traditional Chinese medicine and Western medicine in Alzheimer’s disease: a systematic review and meta-analysis - Wang, Qi; Wang, De-Long; Zhang, Xiu-Chu; Jiang, Xin-Yu; Jiang, Huan-Ning; Yang, Xue-Ying; Zhang, Te; Lv, Yu-Ying; Li, Quan (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to compare the efficacy and safety of traditional Chinese medicine (TCM) compounds with single Western medicines in treating Alzheimer’s disease (AD) through a systematic review and meta-analysis.MethodsIn this study, we searched for randomized controlled trials on the treatment of AD with TCM compounds published before March 2025 in Chinese and English databases (PubMed, Embase, Cochrane, China National Knowledge Infrastructure, VIP, and Wanfang) and conducted a meta-analysis using Stata15.0 software.ResultsA total of 23 studies were included, involving 2,035 participants (1,173 in the experimental group and 862 in the control group). Traditional Chinese herbal compounds showed good clinical efficacy and maintenance effects in the treatment of AD. The effective rate of TCM compounds in treating AD was higher than that of Western medicine (relative risk ratio = 1.19, 95% CI: 1.04–1.37, p = 0.009). In terms of the Alzheimer’s Disease Assessment Scale-Cognitive and Hierarchic Dementia Scale-Revised scores, TCM compounds were superior to Western medicine (standardized mean difference = −0.22, 95% CI: −0.40−−0.05). There were no significant differences between the two groups in the Mini-Mental State Examination or Activities of Daily Living scores. Additionally, there were no significant differences in adverse reactions between the TCM compounds and Western medicine groups.ConclusionThe present research indicates that TCM compounds could be a promising therapeutic option for AD, demonstrating encouraging results in terms of efficacy and safety, particularly regarding certain cognitive functions.